Video streaming based on frame skipping and interpolation techniques - Fadlallah , Fadlallah Ali; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (IJISET, 2016)
in this paper we proposed a video frame skipping and interpolation (VFS-I) techniques to streaming video. This technique is divided into main section: transmitter and receiver. The transmitter is employed Frame Skipping Mechanism (FSM) to drop/skip similar frames from video streaming sequence to reduce the amount of frames that need to be transferred over the network. This method specified frames to-be-kipped according to motion estimation between every neighboring frame. After that, reencode the remaining video frames, and sent it to the receiver. The receiver employed Reconstructing video-Frames Interpolation (RFI) to rebuild the frames that were dropped in the transmitter side. The motion compensated interpolation of the key-frame (remaining frame) is used to reconstruct video frames back. A unified design of frame-skipping and interpolation mechanism are made for incrementing and improving compression process efficiency that have not considered in the previous works. One of the main advantages of the VFS-I is characterized by flexibility and scalability of video streaming to the requirements of the network bandwidth and end user.